The Influences of Digital Promotion, Groups Reference, and Efficacy on The Trust-Mediated Decision to Vaccinate Covid-19 Booster in Balikpapan City - Nur Ali, Deni; Zulfitri Zulfitri (Dinasti Publisher, 2023)
This study aims to examine and analyze the effect of Digital Promotion, Reference Groups, and Efficacy on the Decision to Conduct Covid-19 Booster Vaccination Mediated by Trust (Study in Balikpapan City). This study uses a causal research method. The population in this study are people who have carried out the second vaccine in the city of Balikpapan. The sampling method employs a non-probability sampling technique with 200 respondents from the city of Balikpapan. SEM (Structural Equation Modeling) SmartPLS version 3.0 was used for data analysis. The results showed that: (1) Digital Promotion, Reference Group, Efficacy, and Trust had a positive and significant effect on booster vaccination decisions, (2) Digital Promotion and Reference Group had a positive and not significant effect on Trust, (3) Efficacy had a positive and significant effect on Trust, (4) Trust does not mediate Digital Promotion and Reference Groups on vaccination decisions, (5) Trust mediates efficacy directly or indirectly in influencing booster vaccination decisions.